Bisphenol A (BPA) Found in Humans and Water in Three Geographic Regions with Distinctly Different Levels of Economic Development. (January 2014) - Karalius, Vytas P.; Harbison, Justin E.; Plange-Rhule, Jacob; Van Breemen, Richard B.; Li, Guannan; Huang, Ke; Durazo-Arvizu, Ramon A.; Mora, Nallely; Dugas, Lara R.; Vail, Lane; Tuchman, Nancy C.; Forrester, Terrence; et al.
The suspected endocrine disruptor bisphenol A (BPA) is associated with the manufacture, distribution, and use of epoxy resins and polycarbonate plastics; thus, studies of this compound have focused primarily on urban areas in developed countries. This small study investigating urinary BPA of 109 people was conducted in the urban United States, urban Jamaica, and rural Ghana. Additionally, local drinking and surface water samples were collected and analyzed from areas near study participants. Levels of BPA in both urine and water were comparable among all three sites. Thus, future studies of BPA should consider expanding investigations to rural areas not typically associated with the compound.